Narrative Inquiries of EFL Teachers Agency in the Development of Professional Identities - Nuri Ma’rifatil Laili; Nunung Suryati; Niamika El Khoiri (Graduate School of Universitas Negeri Malang, 2022)
Abstract: This paper aims to explore how EFL teachers manifest their agency in the development of professional identities. The study is narrative inquiry involving eight EFL teachers from Madrasah around Indonesia. Data were collected through narrative frames followed by in-depth interview to clarify blurred stories written in narrative frames. The data were analyzed and elaborated into three themes, the novices, beyond the shell: the journey to be professional teachers, and the lifelong learners. The result shows that the dynamic change enacted by Madrasah EFL teachers can be categorized into three dimensions, the iterational, the practical evaluative, and the projective dimension.